2020
DOI: 10.1093/aob/mcz212
|View full text |Cite
|
Sign up to set email alerts
|

The domestication syndrome in vegetatively propagated field crops

Abstract: Background Vegetatively propagated crops are globally significant in terms of current agricultural production, as well as for understanding the long-term history of early agriculture and plant domestication. Today, significant field crops include sugarcane (Saccharum officinarum), potato (Solanum tuberosum), manioc (Manihot esculenta), bananas and plantains (Musa cvs), sweet potato (Ipomoea batatas), yams (Dioscorea spp.) and taro (Colocasia esculenta). In comparison with sexually reproduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
126
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(134 citation statements)
references
References 124 publications
1
126
1
6
Order By: Relevance
“…Dioscorea alata harboured very low nucleotide diversity in comparison to potato diploid landraces ( Hardigan et al , 2017 ) or cultivated and wild cassava ( Ramu et al , 2017 ). It is also generally recognized that the reduction in sexual fitness is a domestication trait in asexually propagated crops ( Meyer and Purugganan, 2013 ; Denham et al , 2020 ), as recently shown in potato ( Hardigan et al , 2017 ). Consequently, despite the absence of identified wild relatives, based on the narrow nucleotide diversity, the high number of clonal lineages and the scarcity of flowering observed in the field, we could reasonably deduce that greater yam has undergone a strong domestication bottleneck.…”
Section: Discussionmentioning
confidence: 95%
“…Dioscorea alata harboured very low nucleotide diversity in comparison to potato diploid landraces ( Hardigan et al , 2017 ) or cultivated and wild cassava ( Ramu et al , 2017 ). It is also generally recognized that the reduction in sexual fitness is a domestication trait in asexually propagated crops ( Meyer and Purugganan, 2013 ; Denham et al , 2020 ), as recently shown in potato ( Hardigan et al , 2017 ). Consequently, despite the absence of identified wild relatives, based on the narrow nucleotide diversity, the high number of clonal lineages and the scarcity of flowering observed in the field, we could reasonably deduce that greater yam has undergone a strong domestication bottleneck.…”
Section: Discussionmentioning
confidence: 95%
“…Certainly, it has been suggested that vegetative reproduction during domestication can lead to the loss of sexual reproductive capacity 2 , and that flowering and seed development are important characteristics that differentiate cultivated and wild enset 5 . Wild enset flowers more frequently has larger flowers (mean basal girth 186 cm) than cultivated enset (mean basal girth 106 cm) 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Plant domestication and breeding can alter and shrink genetic diversity 1 . In some crop species, this entails a shift from sexual to vegetative propagation 2 . Enset ( Ensete ventricosum (Welw.)…”
Section: Introductionmentioning
confidence: 99%
“…Domestication syndrome traits in vegetative crops represent tendencies in human-mediated plant evolution that reflect a combination of permanent genetic changes and impermanent plastic responses to cultivation practices. Thus, vegetative propagation enables more controlled selection of favored phenotypic characteristics than under sexual reproduction (Denham et al, 2020). Conversely, no bottlenecks were identified from the wild genetic pool in Central Asia to European, Southern Central Asia and Chinese cultivated apricots (Decroocq et al, 2016;Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This is probably explained by the limited number of generations since domestication due to long juvenile phases, ongoing gene flow between domesticated and wild accessions (Miller and Gross, 2011;Gaut et al, 2015) and, to a lesser extent, to clonal propagation (because it is difficult to carry out on apricot species in comparison with plum, peach, apple and grape). Recently, Denham et al (2020) attested that spontaneous sexually reproduced progeny may also be incorporated into clonally reproduced crop assemblages thereby enabling gene flow and potentially prolonging the period of domestication.…”
Section: Introductionmentioning
confidence: 99%